P243 Influenza A outbreak in a UK respiratory centre. (14th November 2013) - Aujayeb, A; West, S; Waugh, S; Samuel, J; Russel, A; Fagg, R; Gray, S; Walton, C; Meachery, G
Abstract : Introduction: In March 2013, 12 patients on a single ward in a tertiary respiratory transplant centre contracted influenza within 72 hours. There was no corresponding community outbreak. Staff with symptoms went off sick. Trust policies outlining respiratory infection and isolation existed but there were no guidelines for this specific novel situation. We found no published reports of such an event in England. Methods: Patients quickly developed pyrexias and respiratory symptoms. All had throat swabs and blood cultures. Influenza A, H3N2 variant, was identified. A team of infection control and respiratory physicians, nurses and managers met regularly to implement these measures: Closure of ward and cohorting of bays Ward avoidance for non-essential personnel and anyone with symptoms Cancellation of non-essential procedures Strict hand hygiene and use of PPE and FFP3 masks Stockage of oseltamivir for treatment for all affected high risk staff and patients and prophylaxis offered to all ward patients and exposed high risk staff. No crossover of ward staff to transplant patients. Contact tracing of all immunocompromised patients on ward up to one week and all high risk patients 48 hours prior to the index case; advice on prophylaxis and their GPs contacted. Writing an information sheet for staff and GPs Increased and terminal ward cleaning Results: On the respiratory ward, 151 bed days were lost and 53 on two other wards. Fourteen patients (including two on another ward) had positive swabs for H3N2. There were 27 symptomatic staff members; 15 had swabs, two were positive. All patients and two staff members were given treatment oseltamivir. Fourteen patients and two staff members had prophylaxis. No influenza complications or deaths occurred. The department staff had 45% influenza vaccination uptake in 2012/2013. All affected patients had been vaccinated. Conclusions: Containment, pathogen identification, prompt treatment and contact tracing were priorities, to limit number of individuals affected. This is widely applicable. Our departmental staff vaccination rate is below Department of Health targets. Importance of vaccination needs emphasising, whilst recognising that vaccine effectiveness against all laboratory-confirmed influenza in primary care is 51% for 2012/2013.